Factors that Influence Behavioral Intention of Digital Financial Transactions on the Millenial Generation in Palembang - Mia Audina; Isnurhadi Isnurhadi; Isni Andriana (Budapest International Research and Critics University, 2022)
This study aims to examine and analyze the factors that influence behavioral intention in using digital financial transaction services (E-wallet) by millennial generation in Palembang City by using the unified theory of acceptance and use of technology 2 (UTAUT2) and expanded by adding digital financial literacy variable. This study used purposive sampling technique. Data for 250 millennial generations using ShopeePay, GoPay, and DANA E-wallet in Palembang City were obtained through an online questionnaire survey. The data then were analyzed using Partial least square-structural equation modeling (PLS-SEM). The results showed that performance expectancy, social influence, hedonic motivation, and digital financial literacy had a positive and significant influence on behavioral intention. Meanwhile, effort expectancy and facilitating conditions did not have a significant influence. Future research is expected to add other factors not included in this study, such as price value and habit.